Modelling the Initial Stages of Condensation of As-S Atomic Clusters - Dalekorej Anatolij; Victor Kovtunenko; Stoika Myroslav; Sztojka Miroszláv; Далекорей Aанатолій; Віктор Ковтуненко; Стойка Мирослав (Сумський державний університет, 2018)
Abstract. With the use of first-principle quantum-mechanical method DFT the initial phases of condensation processes of 4- and 5-atomic AsnSm clusters on the carbon substrate have been studied. It has been determined that due to the break of one or two chemical bonds most clusters during adsorption on the surface of the carbon substrate are transformed from their initial structural shapes into the chain whose ends are covalently bonded with the substrate. The calculated adsorption energies of such clusters on the carbon substrate are equal to 1.7-1.9 eV/atom. Pentagon-shaped S5, As2S3 and As4S clusters are also highly likely to be adsorbed on the carbon substrate without the change of their spatial shape under the influence of van der Waals forces. For As4 clusters-molecules such adsorption mechanism is the main one. The energy of such adsorption of clusters is 0.4-0.5 eV/atom. It has been determined that the energy and mechanism of adsorption of AsnSm clusters are significantly affected by the dynamics of changes in internal tensions of the atomic system before and after adsorption. Such effect may be more significant in case of adsorption not on the model, but on real, more “rigid” carbon substrates.
https://jnep.sumdu.edu.ua/uk/component/content/full_article/2517
Keywords: adsorption; chalcogenide clusters; first-principle modelling; adszorpció; chalcogenide klaszterek; első elvű modellezés; адсорбція; кластери халькогенідів; моделювання за першим принципом